On spermatophore-producing aquatic microdrile oligochaetes (Annelida: Clitellata) - Rodriguez, Pilar; Fend, Steven V. (Zootaxa, 2018)
The formation of encapsulated spermatophores is exceptional among aquatic oligochaetes, although it seems to have occurred independently in several unrelated taxa. Among the microdriles, some variations appear unique to single species. The recently described lumbriculid Uktena riparia Fend et al. forms spermatophores in the male duct and attaches them within a deep spermathecal bursa. The attachment of spermatophores to the body wall, in the clitellar region, or in the vicinity of male or spermathecal pores has been reported in Paranadrilus Gavrilov, Bothrioneurum Štolc and some Aktedrilus Knöllner species. Anatomical comparison of reproductive organs suggests convergent development of glandular organs in the male duct or spermathecae, used for the formation, transfer and/or attachment of spermatophores to the concopulant worms. The presence of similar organs in Smithsonidrilus Brinkhurst, where spermatophores have not been reported, is also discussed. Furthermore, a lectotype is designated for Paranadrilus descolei Gavrilov, 1955.